Noble gases in Yamato-791197: Evidence for lunar highland origin - Takaoka, Nobuo (1986)
P(論文) Concentrations and isotopic compositions of five stable noble gases were determined for a whole rock sample and a white clast prepared from the Yamato-791197 breccia. The whole rock contains large amounts of trapped gases originating from solar wind implantation. Relative elemental abundances and isotopic compositions of trapped gases indicate the possible origin of the Y-791197 meteorite from lunar highland regolith. The high concentrations of both trapped and spallogenic gases in the whole rock and the cosmogenic ^<131>Xe/^<126>Xe ratio in the white clast suggest that the meteorite resided at a low average cosmic-ray shielding less than 65g/(cm)^2. An exposure age of 910±60 Ma is tentatively estimated for the whole rock, whereas the exposure age for the white clast is shorter by a factor of about three. departmental bulletin paper